Novel active compounds and the anti-diabetic mechanism of mulberry leaves - Lv, Qiuyue; Lin, Jinrong; Wu, Xinyan; Pu, Huanhuan; Guan, Yuwen; Xiao, Peigen; He, Chunnian; Jiang, Baoping (Frontiers in Pharmacology, 2022)
Mulberry (Morus alba L.) leaves have long been considered beneficial in traditional Chinese medicine to treat infectious and internal diseases. Recently studies have discovered that the mulberry leaf’s total flavonoids (MLF) display excellent hypoglycemia properties. However, the active ingredients and their molecular mechanisms are still uncharacterized. In this study, we explored the hypoglycemic effects of MLF and mulberry leaf polysaccharides (MLP) on ob/ob mice, an animal model of type 2 diabetes mellitus (T2DM), compared with Ramulus Mori (Sangzhi) alkaloid (RMA). Network pharmacology was employed to identify the potential available targets and active compounds of MLF and RMA against hyperglycemia. Molecular docking, an insulin-resistant cell model and qPCR were employed to verify the antidiabetic activity of the critical compounds and the gene expression profiles of the top molecular targets. Here, the results showed that MLF and MLP improved glucose uptake in insulin-resistant hepatocytes. MLF, MLP and RMA alleviated insulin resistance and glucose intolerance in ob/ob mice. Unlike MLF and MLP, RMA administration did not influence the accumulation of intrahepatic lipids. Network pharmacology analysis revealed that morusin, kuwanon C and morusyunnansin L are the main active compounds of MLF and that they amend insulin resistance and glycemia via the PI3K- Akt signaling pathway, lipid and atherosclerosis pathways, and the AGE-RAGE signaling pathway. Moreover, 1-deoxynojirimycin (DNJ), fagomine (FA), and N-methyl-1-deoxynojirimycin are the primary active ingredients of RMA and target carbohydrate metabolism and regulate alpha-glucosidase activity to produce a potent anti-diabetic effect. The molecular docking results indicated that morusin, kuwanon C and morusyunnansin L are the critical bioactive compounds of MLF. They had high affinities with the key targets adenosine A1 receptor (ADORA1), AKT serine/threonine kinase 1 (AKT1), peroxisome proliferator-activated receptor gamma (PPARγ), and glycogen synthase kinase 3 beta (GSK3β), which play crucial roles in the MLF-mediated glucose-lowering effect. Additionally, morusin plays a role in amending insulin resistance of hepatocytes by repressing the expression of the ADORA1 and PPARG genes. Our results shed light on the mechanism behind the glucose-lowering effects of MLF, suggesting that morusin, kuwanon C, and morusyunnansin L might be promising drug leads for the management of T2DM.